Purification, crystallization and preliminary X‐ray analysis of the AAA+σ54 activator domain of FlrC from Vibrio cholerae. Issue 7 (22nd July 2013) - Dey, Sanjay; Dasgupta, Jhimli
<x xml:space="preserve">Abstract</x> A σ54‐dependent transcriptional activator FlrC containing an N‐terminal regulatory domain, a central AAA+ domain and a C‐terminal DNA‐binding domain has been implicated both in flagellar synthesis and enhanced intestinal colonization. FlrC is phosphorylated by the kinase FlrB at the regulatory domain and both nonphosphorylated and phosphorylated states of FlrC seem to be important for its functions. Oligomerization plays a key role in the functions of such transcriptional activators and the AAA+σ54 interaction domain is critical in deciding the oligomerization state. Therefore, to obtain structural insights into FlrC at the atomic level, the AAA+σ54 interaction domain of FlrC was cloned, overexpressed and crystallized using PEG 6000 as precipitant at pH 6.0, and diffraction data were collected to 2.8 Å resolution. Molecular‐replacement calculations and subsequent refinement confirmed the presence of a closed heptamer in the asymmetric unit.